Complications after implantation of a new-generation insertable cardiac monitor: Results from the LOOP study. (15th August 2017) - Diederichsen, Søren Zöga; Haugan, Ketil Jørgen; Højberg, Søren; Holst, Anders Gaarsdal; Køber, Lars; Pedersen, Kenneth Bruun; Graff, Claus; Krieger, Derk; Brandes, Axel; Svendsen, Jesper Hastrup
Abstract: Background: Insertable cardiac monitors (ICM) are leadless devices utilized in long-term monitoring of the heart rhythm. The implantation procedure of the new-generation ICMs is minimally invasive, but little experience exists regarding complications. We thus aimed to investigate adverse events (AE) according to procedure-related characteristics after implantation of a large number of new-generation ICMs. Methods: The study population consisted of participants randomized to receive ICM in a multi-center trial. The Reveal LINQ™ ICM was implanted using provided insertion tools, either in an electrophysiology laboratory or outpatient procedure room. If device sensing was insufficient in the first subcutaneous position, one or more repositions were performed. Patients were urged to make contact if they suspected any AE. Furthermore, follow-up for safety endpoints consisted of evaluation of medical records and planned study visits. Results: 1420 patients received an ICM, 753 (53%) in a procedure room and 667 (47%) in an electrophysiology laboratory. During a median follow-up of 499 days, 9 (0.63%) and 15 (1.13%) patients experienced AEs with and without need for device explantation, respectively. In the 38 patients requiring device repositioning, more AEs requiring explantation were seen (3 (7.9%) vs. 6 (0.4%), p  = 0.001). Patients undergoing implantation in a procedure room had more infections (12 (1.6%) vs. 1 (0.1%), p  = 0.004), though no significant difference was reached in AEs requiring explantation (7 (0.9%) vs. 2 (0.3%), p  = 0.19). Conclusion: The Reveal LINQ™ ICM can be inserted with a very low risk of complications, both in the traditional electrophysiology laboratory setting and in an outpatient procedure room.